Pengembangan E-Lkpd Matematika Berbasis Project Based Learning Di Sekolah Penggerak - Eni Defitriani (Universitas Batanghari Jambi, 2026)
This study develops an electronic learning material (e-LKPD) for mathematics based on Problem-Based Learning (PBL) at Sekolah Penggerak. The development uses the 4D model (Define, Design, Develop, Dissemination). Students of SMA Negeri 7 Kota Jambi served as the research subjects. The results show that the developed e-LKPD has high validity and practicality. Expert validation reached 83.63% (content), 90% (design), and 96.36% (media). Meanwhile, teacher and student responses indicated practicality of 87.5%.